Examining the efforts of the Aceh Government in dealing with child victims of sexual violence - Nashriyah, Nashriyah; Alfiatunnur, Alfiatunnur; Hermawan, Tya D.J. (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2021)
The increasing incidence of violence against children, especially cases of sexual violence in Aceh, has raised questions about the performance of the Aceh government stakeholders in handling this case. Based on this, this study seeks to examine: 1) the efforts having been made by the Aceh government in dealing with cases of sexual violence against children and 2) the constraints of the Aceh government in coping with cases of sexual violence against children. This field research was designed in a qualitative descriptive manner using analytical research methods. There were eight purposively selected informants who were used as a source of data for this research. The techniques to collect data were observation, interviews and documentation studies. The techniques used in processing and analysing the data were data reduction, data display and conclusion drawing/verification. The findings indicated that the efforts made by the Aceh government in overcoming the problem of sexual violence in Aceh, especially against children, are prevention, handling and empowerment efforts through socialization and other efforts that involve various parties. In addition, there is special treatment for the victim and the perpetrator. Furthermore, the results of the study also revealed that there are three main aspects that become obstacles in overcoming cases of sexual violence against children, namely from the community, bureaucracy and Aceh government agencies.